Ще раз про Старосільський скарб доби пізньої бронзи з Черкащини - Куштан, Д.П. (Археологія і давня історія України, 2020)
У статті повторно публікується скарб доби
пізньої бронзи, виявлений в с. Старосілля Городищенського р-ну Черкаської обл. Вперше його ввів у
науковий обіг Д. Я. Телегін у 1982 р. До складу комплексу входять п’ять предметів із бронзи: двовушковий кельт, два безвушкових кельти, жолобчасте долото та цільнолитий браслет. Thirty eight years ago the set of bronze tools found
near the Starosillia village in Gorodyshche district
of Cherkasy region has been published. This Late
Bronze Age deposit remains one of the most known in
the region. Three «celts», sleeve chisel and cast bracelet
were preserved till the present time (fig. 1). These
finds are kept in the Cherkasy Museum of local history.
Starosillia deposit is important in terms of identification
of main intercultural connections and contacts
in the late 2nd mil. BC. The evidence, obtained over the
last several dozen years, makes possible the new attribution
of finds, their typology, area of spread and dating.
Besides this, new publication of Starosillia deposit
with drawing and photos of a high quality (it should
be noted that the article of D. Telegin is lacking the
drawing of one «celt») is required. This is why we need
to turn back to the deposit.
Two «celts» belong (fig. 3, 4) to the Dichevo type
(Oinacu variant) according to V. Dergachev. Their
origin is linked to Lower Danube center, from where
these tools were spread in the North Pontic region, the
area of Noua and Sabatynivka (later — early Bilozerka)
cultures. Double-eyelet «celt» (fig. 2) belongs to
Kardashynka type according to V. Dergachev. Such
tools were used in late Sabatynivka and early Bilozerka
time. In case of the analyzed region, such tools
are referred to populations of Bilozerka culture, while
the related molds were mainly found in the Lower
Dnieper region. This is also the case of sleeve chisels
(fig. 5) which are being similar to the find from Starosillia.
Cast bracelet (fig. 6) from the deposit is typical
for Sabatynivka and Bilozerka cultures, from which
such bracelets could spread to the area of Bilogrudivka
culture. Thus, the deposition of Starosillia deposit
may be dated to the early Bilozerka time (HaA1),
12th century BC, when the Middle Dnieper region
was inhabited by populations of Bilogrudivka culture.